Hybrid project learning and peer teaching as learning strategies for learners with high activity - Fakhris Khusnu Reza Mahfud; Zainal Abidin; Usman Nurhasan (University of Merdeka Malang, 2024)
The mosque is the Muslim community's place of worship and education. Regular worship occurs according to a timetable. However, educational activities require quite a long time, so the mosque management schedules learning activities periodically. In addition, mosque congregations have a very high diversity and density of activities, especially mosque congregations in urban areas. The management of urban mosques has difficulty organizing learning consistently because the congregation has difficulty meeting at the same time periodically. This paper offers a solution by teaching with a hybrid learning method between project learning and peer teaching. Projects are created based on the needs of the environment and the congregation. The project development team is formed from worshipers who can work on projects. Other congregants receive knowledge through the project development team when the project is in the process of being created and run. This hybrid learning was experimented with by creating an aquaponics project. Aquaponics is operated with solar electricity. The project development team consists of a congregation of children to parents. The project has successfully transferred knowledge to the project development team members. The project operation attracts non-team worshippers to discuss independently with team members. Some non-team members have developed fish farming independently.